A coisa julgada no código de processo civil de 2015 : premissas, conceitos, momento de formação e suportes fáticos - Senra, Alexandre (2016)
The research deals with the res judicata in the Civil Procedure Code of 2015 (CPC/15), from a normative perspective. It is divided basically into two parts. In the first part, are exposed the author's premises. The legal phenomenon is examined, according the theory of legal fact, in the level of general theory of law. The language of positive law is differentiated from the language of science of law, based on three criteria: hierarchy, type and function. Words, concepts and definitions are distinguished from each other and articulated. The second part develops the theme (res judicata). After examining the main concepts of res judicata developted and used by the doctrine and making a first confrontation between them and the CPC/15, the concepts of res judicata that the author considers useful to the understanding of the matter, as regulated by CPC/15, as designed and defined. Then, the attention is turned to the Constitution, so that the constitutional limits for the legislative activity on the subject are verified, prior to a deeper examination of the rules inside the CPC/15. After that, it analyzes the initial moment of res judicata in various situations. Finally, the longest chapter examines the types of legal facts that produce the legal effect res judicata. They are analyzed from three categories, which the author calls: "res judicata on main issues", "res judicata on procedural matters" and "res judicata on incidental prejudicial questions."